Constructivist approach to multimedia design for interactive content in discrete mathematic (permutation and combination) / Adzlan Ahmad - Ahmad, Adzlan (2005)
Most of students who learn Additional Mathematics in higher secondary school and the high institute of education students who study Discrete Mathematics found that the topic of probability is very boring and difficult to learn. In official examination such as Sijil Pelajaran Malaysia (SPM) in Additional Mathematic subject, the questions related of probability will be skipped by most students. Moreover, the questions about probability are optional. It is because from their opinion, this topic is hard to learn especially in conventional way. It influenced some teachers to do not teach this topic. Another problem traced is the students feel hard to recognize the type of probability problems which will be using permutation method and which kind of questions will be using combination method. The process of designing of the prototype of courseware is more focus to Permutation and Combination, one of the topics in Discrete Mathematics and also in Additional Mathematics. This courseware is developed for not only the students who take that course, but also suitable for anyone who did not know before about probability. In designing this courseware, the examples and questions will be constructed based on the learning theory that is constructivism approach. The courseware will be following the constructivism theory which the students will be able to construct the solutions and finally will come up with general ideas of what they have learned. Besides of that, the examples of the problem will be provided and suited the each subtopic which they will learn.